Water, sanitation, and hygiene access among people who inject drugs in Tijuana and San Diego in 2020-2021: a cross-sectional study - Alhelí Calderón-Villarreal; Lourdes Johanna Avelar Portillo; Daniela Abramovitz; Shira Goldenberg; Shawn Flanigan; Penelope J. E. Quintana; Alicia Harvey-Vera; Carlos F. Vera; Gudelia Rangel; Steffanie A. Strathdee; Georgia L. Kayser (BMC, 2024)
Abstract Background Water, sanitation, and hygiene (WASH) access is critical to public health and human dignity. People who inject drugs (PWID) experience stigma and structural violence that may limit WASH access. Few studies have assessed WASH access, insecurity, and inequities among PWID. We describe WASH access, social and geographic inequalities, and factors associated with WASH insecurity among PWID in the Tijuana-San Diego metropolitan area. Methods In this cross-sectional binational study, we interviewed PWID (age 18+) in 2020-2021 about WASH access and insecurity. City of residence (Tijuana/San Diego) and housing status were considered as independent variables to describe key WASH access outcomes and to assess as factors associated with WASH insecurity outcomes. Measures of association between outcomes and independent variables were assessed using log modified-Poisson regression models adjusting for covariates. Results Of 586 PWID (202 Tijuana; 384 San Diego), 89% reported basic access to drinking water, 38% had basic hand hygiene, 28% basic sanitation, and 46% access to bathing, and 38% reported recent open defecation. Participants residing in Tijuana reported significantly higher insecurity in accessing basic drinking water (aRR: 1.68, 95%CI: 1.02-2.76), basic hygiene (aRR: 1.45, 95%CI: 1.28-1.64), and bathing (aRR: 1.21, 95%CI: 1.06-1.39) than those living in San Diego. Participants experiencing unsheltered homelessness experienced significantly higher insecurity in accessing basic drinking water (aRR: 2.03, 95%CI: 1.07-3.86), basic sanitation (aRR: 1.68, 95%CI: 1.48, 1.92), bathing (aRR: 1.84, 95%CI: 1.52-2.22), and improved water sources for cleaning wounds (aRR: 3.12, 95%CI: 1.55-6.29) and for preparing drugs (aRR: 2.58, 95%CI: 1.36-4.89) than participants living in permanent housing. Conclusion WASH access among PWID in the Tijuana-San Diego metropolitan area was low by international standards and lower than the national averages in both countries. Homelessness was significantly associated with WASH insecurity in this population. Concentrated efforts are needed to guarantee continuously available WASH services for PWID-especially those who are unsheltered.